V994 Herculis: a unique triply eclipsing sextuple star system. Issue 2 (31st January 2023) - Zasche, P; Borkovits, T; Jayaraman, R; Rappaport, S A; Brož, M; Vokrouhlický, D; Bíró, I B; Hegedüs, T; Kiss, Z T; Uhlař, R; Schwengeler, H M; Pál, A; et al.
ABSTRACT: We report the discovery with the Transiting Exoplanet Survey Satellite ( TESS ) of a third set of eclipses from V994 Herculis (V994 Her, TIC 424508303), previously only known as a doubly eclipsing system. The key implication of this discovery and our analyses is that V994 Her is the second fully characterized (2+2) + 2 sextuple system, in which all three binaries eclipse. In this work, we use a combination of ground-based observations and TESS data to analyse the eclipses of binaries A and B in order to update the parameters of the inner quadruple's orbit (with a derived period of 1062 ± 2 d). The eclipses of binary C that were detected in the TESS data were also found in older ground-based observations, as well as in more recently obtained observations. The eclipse timing variations of all three pairs were studied in order to detect the mutual perturbations of their constituent stars, as well as those of the inner pairs in the (2 + 2) core. At the longest periods they arise from apsidal motion, which may help constraining parameters of the component stars' internal structure. We also discuss the relative proximity of the periods of binaries A and B to a 3:2 mean motion resonance. This work represents a step forward in the development of techniques to better understand and characterize multiple star systems, especially those with multiple eclipsing components.